Identification of m6A methyltransferase-related WTAP and ZC3H13 predicts immune infiltrates in glioblastoma - Liyun Gao; Jiaxin Gao; Jiayin He; Wenyan Fan; Xiangxin Che; Xin Wang; Tao Wang; Chunhua Han (Scientific Reports)
Abstract Glioblastoma (GBM) is a prevalent and highly fatal primary malignant brain tumor. N6-methyladenosine (m6A) modification plays a critical role in the development of brain tumor. WTAP and ZC3H13 have been identified across various species. Immune contexture, which includes the tumor microenvironment (TME), plays a significant role in cancer progression and treatment. This study aimed to explore the potential impact between WTAP and ZC3H13 on the immunological characteristics of GBM. We utilized data from TCGA-GBM, GEO and CGGA datasets to obtain platform and probe data. Patients with GBM were stratified into two clusters based on the expression of WTAP and ZC3H13 using consensus clustering approach. Immune infiltration within the tumor microenvironment was assessed using ESTIMATE, CIBERSORT and ssGSEA methodologies. Functional disparities were determined through gene set enrichment analysis (GSEA). Tumor mutation burden (TMB) and immune checkpoint inhibitors (ICIs) were also analyzed. Co-expression network analysis (WGCNA) was used to identify genes associated with WTAP/ZC3H13 and immunity. Validation was performed using GEO and CGGA datasets. Our analysis revealed that cluster1 exhibited higher WTAP expression but lower ZC3H13 expression compared to cluster2. Cluster1 showed higher levels of immune infiltration and TMB compared to cluster2. WGCNA identified 15 genes closely associated with WTAP/ZC3H13 expression and immune scores, notably CTLA4, CD27, ICOS, and LAG3. Our results suggested that WTAP and ZC3H13 influence on immune contexture of GBM, providing new insights into tumor immunity in GBM.